Management of Organic Waste Into Eco Enzyme in Ulakan Tapakis Padang Pariaman - Indonesia - Prarikeslan, Widya; Rahmaneli, Rahmaneli; Nora, Desri Nora; Prayoga, Rendi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
his article aims to increase the knowledge of mothers and young women in processing organic waste into useful goods and increase the understanding and ability of the community in terms of waste sorting and management. The visible aspects of the process of sorting organic and non-organic waste. This activity was carried out in Nagari Ulakan, Ulaakan Tapakis District, Padang Pariaman Regency. The participants involved were housewives and young women who were represented by 17 people. The form of activity is conducting training related to waste sorting and conducting training related to managing organic waste into eco enzymes. The implementation stage begins with the preparation stage, stage, and ends at the monitoring and evaluation stage. The results of the training carried out in Nagari Ulakan, Padang Pariaman Regency in the form of environmentally friendly enzymes that can be used in everyday life, such as for house cleaning, fruit and also as fertilizer. From this training, the community understands the benefits generated from organic waste that does not need to be disposed of but can be reused, this can also reduce the amount of waste that is thrown into the landfill every day. Cutting the flow of waste distribution to landfill and waste management is an effective solution and accelerates the processing of waste into more useful products.